Pressure from the East European member states: Tax burdens, locational competition and reform requirements within the EU-25 - Ognian N. Hishow (Stiftung Wissenschaft und Politik (SWP), 2004)
The discussion presently taking place in the large Eurozone economies about the reform of the social welfare state is dominated by two assertions: Western Europe as an investment location is too expensive due to its high tax burden and, second, countless jobs are threatened from low-wage competition from the new EU member states. These claims are only partially true. Whereas the overall tax load in France is above the EU-15 average, the German tax load lies in the middle range. In addition, the export of jobs to new member counties has been declining since 2003. The reforms introduced in the EU and Germany subsumed under the headings of the Lisbon Strategy or Agenda 2010 are not solely in response to EU eastward expansion. Nonetheless, EU extension has contributed to an increased willingness to implement reforms and has stimulated, for example, efforts to adapt the structure of tax revenue in an effort to meet global challenges. It is hardly accurate, however, to speak of a "race to the bottom," which has supposedly been touched off by the new EU members. What is needed is the elimination of obstacles that hamper investment, growth and employment. (SWP-Comments / SWP)
Keywords: 320